Study on the Static Stiffness of Large Diaphragm- rubber Coupling - Wang Zhonghou; Luo Jing; Zhao Bo; Zeng Linxi (Jixie chuandong)
By using the finite element software ABAQUS,the finite element model of large diaphragm-rubber coupling is established,and the simulation and analysis of its static stiffness is carried out,the static torsional stiffness,radial and axial stiffness of the diaphragm- rubber coupling are calculated. Finally,through the establishment of the coupling stiffness calculation model,the calculation method of the contribution amount of couplings rubber block coupling components and the diaphragm components to radial and axial stiffness is proposed,the guidance for further study of the coupling design is provided.